A comparison of the United Kingdom’s Digital Services Tax regime and the OECD Two-pillar approach: Is this unilateral measure hindering the implementation of the Pillar Two model? - Nong, Thato (© University of the Witswatersrand, Johannesburg, 2023)
Base Erosion and Profit Shifting (BEPS) has become the focal point for Multinational Enterprises (MNEs) with the aim of maximising their profits and minimising or totally avoiding their tax payable to a jurisdiction. The goal of this study is to highlight the tax concerns that have arisen as a result of digitisation, which have exacerbated the erosion of the tax base and profit shifting in the United Kingdom from the standpoint of Corporate Income Taxes (CIT). It will examine the Digital Services Tax in further depth, contrast it to the OECD Pillar Two, and provide a proposal on whether the DST impedes a global solution. BEPS has left several governments concerned about their revenue collection regulations, especially as the world commerce economy becomes more computerised. The research methodology used for this study is qualitative and interpretive of the UK's Digital Services Tax Act and the OECD Two- Pillar model. The introduction of the Digital Services Tax in the United Kingdom to tax in- scope earnings is an appropriate interim solution; nonetheless, multinational corporations face the possibility of being double-taxed, with no easily available redress, thus not aligning with global best practices as explained in the study. In order to combat BEPS, the Organisation for Economic Cooperation and Development (OECD), in collaboration with the Group of Twenty (G20) forum and other developing countries, established a two-pillar approach, which, before implementation, will require the rejection of all unilateral measures such as DSTs. This study supports the worldwide proposal that unilateral actions adopted by jurisdictions such as the UK to safeguard their tax base must be opposed in the context of direct taxeS
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation)
Keywords: UCTD; Transfer Pricing; OECD; Dual Residency; Permanent Establishment; Valued Added Tax; Tax Treaties; Modern Tax Framework; Aggressive Tax Planning; Multilateral Conventions; SDG-8: Decent work and economic growth